Factors consumers in Halalan Tayyiban among students in UiTM Puncak Alam / Nurul Izzah Mahbob. - Mahbob, Nurul Izzah (2020)
Halal food is not the main choice for Malay or Islamic Consumers. This is because they are less aware of the concept of halal and less concerned about their food. Most Muslim buyer still give priority to other aspects such as price, taste, packaging and quality. In addition, Muslim consumers still have a poor understanding of the importance of using halal products and goods. This research aim is to analyse the factors of student in Uitm Puncak Alam not choose in Halalan Tayyiban products, to know what the concept of the Consumer in Halalan Tayyiban is, and to study the level understanding of the student in Uitm Puncak Alam about Halalan Tayyiban in their food selection. This research is used quantitative method. Thus, survey questionnaire used to achieve objective for this research, which is to know the understanding and the factors consumers in Halalan Tayyiban among the students in Uitm Puncak Alam. The result of the study also suggested that a give student understanding concept of Halal and illegal with promotes activities, or programs related to halal nutrition and prevents them from consuming obscure foods with no legal halal status. Some of the activities that be done such as lectures or pamphlets being distributed to teens and gives talk to them about the information of health halal nutrition food.